LEARNING IN THE CLASSROOM: DOES THE ACT OF ASKING, EXPERIENCING AND REUSING PRESERVE THE ENVIRONMENT? - Aparecida Ribeiro de Oliveira , Juliana; Marcelo Cavalheiro Félix , Carlos; Pereira de Oliveira, Valquiria (Revista Gênero e Interdisciplinaridade, 2026)
The present study presents a pedagogical practice in a project-study format, carried out with two fourth-year classes in a public Basic Education school. The objective was to develop globalized projects in Elementary School - Early Years -, creating greater awareness among students and the school community regarding sustainable environmental practices, prioritizing the reuse of cooking oil. The methodology used qualitative research with a case study approach. From the empiric fabric of concepts, the students and teacher-researchers held a workshop in which they made bars of soap, reusing saturated oil. The results of the study project indicate that: students learned the step-by-step process of scientific research; the teacher-researchers mediated the study, allowing the act of asking, experimenting and reusing; soap making enhanced empirical research; The soap from the experiment was approved by the families who received the samples and then carried out their evaluation.